The State of Aceh Before The Earthquake Driven Tsunami: Some Preliminary Research Notes - EM Yusuf Iis (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2011)
This article would like to give a concise background of Aceh for The BRRs [Badan Rekonstruksi dan Rehabilitasi, The Agency for Reconstruction and Rehabilitation] Proposal for Transformation and Sustainable Development which is framed, bringing together the goals and aspirations of many groups and sectors from Aceh society just in time of Islamic Sharia law initiated. In initiating this process, it assumed an enormous challenge, to seek a national consensus in a local government where the imposition of ideas has prevailed over dialogue and negotiation, frequently leading to force and violence. Aceh and Nias Reconstruction and Rehabilitation Agency BRR is the sole agent for redevelopment of Aceh and Nias and without any public hearing or consultation, they are conducting many project of development in the aftermath of tsunami disaster in the region.